An evaluation of the responses of some tea clones to environment in Kenya - Ng'etich, Wilson Kipkoech (Cranfield University, 1995)
An experiment set up at four sites in Kericho, Kenya was used to investigate Genotype x Environment interactions of four tea clones of commercial and scientific interest. Small differences in environment resulted in large variations in dry matter production and yield between sites and clones. The largest dry matter was from clone TNI 4/3 (291 ha'1) but it had low yield (2.11 ha'1/ 1). By contrast, the largest yield was from clone S15/10 (3.81 h a 'V 1), which gave the smallest dry matter ( I S th a 1). These contrasting responses in dry matter and yield were analysed in terms of the interception of solar radiation, radiation use efficiency, partition of dry matter and components of yield. The differences in clonal dry matter production were attributed to site to site variability in solar radiation and temperature which affected the rates of ground cover development and the solar radiation interception. The differences in yield were attributed mainly to differences in air temperature and saturation deficits of the air between the sites which affected the shoot replacement cycles through rates of shoot extension and development. Differences in measured and derived environmental variables between the sites were found. Incident solar radiation differed between the sites by up to 2.4M Jm 2 d 1. Differences in mean air and soil temperatures between the extreme sites were 2.5 °C and 3 °C respectfully. A lapse rate of 6.1 “Ckm*1 for mean air temperature was found. Annual rainfall amounts also differed between the sites by up to 700 mm. There were no differences in wind speeds, but there were large differences were in saturation deficits (0.5 kPa) and évapotranspiration (1 mm d*1). During the course of the experiment light interception ranged from less than 5% at planting to more than 80% in April 1994. Radiation use efficiencies for dry matter ranged from 0.30 to 0.45 g MT1 in the clones studied and appeared conservative with respect to temperature across the sites. Clone TNI4/3 had the lowest base temperature for shoot extension (6.1 °C), while clone BB35 had the highest (10.4 °C). The base temperatures for shoot extension were 1.3 to 2.9 °C higher than those for development, hence the differences in shoot lengths between sites. Shoot replacement cycle ranged from 57 days to 110 days between the sites and was the main determinant of yield. Abstract Silsoe College WK Ng’etich PhD. 1995 CranfisM,m The dry matter content of shoots varied between sites and seasons and ranged from 18% to 33%. Mean shoot dry mass was inversely proportional to temperature, ranging from 6 to 12% difference between extreme sites. Loss in yield due to water stress during the dry seasons ranged from 14 to 20% across the sites. Yield losses due to ‘hut sites’ ranged from 10 to 50%, while that from hail damage accounted for up to 20% of annual yields. These results are discussed in the light of other work in Kericho and southern Tanzania. The thesis concludes by considering the implication of the results for the tea industry.